Analisis Kajian Filsafat: Integrasi Nilai Kejujuran Dalam Kurikulum Pendidikan - Dita Puspita Dewi; Mad Ali (Journal of Practice Learning and Educational Development, 2025)
The study aims to provide a philosophical foundation for character education development in Indonesia, advocating for a value-based curriculum that fosters integrity in students. This study explores the integration of the value of honesty into the educational curriculum through a philosophical framework involving ontology, epistemology, and axiology. Honesty as a central tenet in Islamic teachings and character education, faces significant challenges in its implementation in the modern era, particularly with the pervasive influence of digital culture and the weakening of moral awareness. Employing a qualitative approach, this research utilizes a literature review to examine various sources related to education and philosophy. The findings suggest that the integration of honesty should not be limited to teaching materials but must permeate school culture through role modeling by educators and the habitual practice of honest behavior. A curriculum emphasizing honesty can contribute to producing individuals who are intellectually competent and morally upright.